Utility of immunology, microbiology, and helminth investigations in clinical assessment of severe asthma. (15th February 2022) - Singer, Andrew; Ali, F. Runa; Quantrill, Simon; North, Nathan; Stevens, Mike; Lambourne, Jonathan; Grigoriadou, Sofia; Pfeffer, Paul E.
Abstract: Objective: Systematic assessment of patients with potential severe asthma is key to identification of treatable traits and optimal management. Assessment of antimicrobial immune function is part of that assessment at many centers although there is little evidence-base on its added value in clinical assessment of this patient group. As part of reviewing our local pathway, we have retrospectively reviewed these tests in 327 consecutive referrals to our severe asthma service, in an evaluation to describe the utility of these tests and allow refinement of the local guideline for patient assessment. Methods and Results: Serum immunoglobulin concentrations were in the normal range in most patients though 12 patients had serum IgG < 5.5 g/L and many had suboptimal anti-Haemophilus (127 of 249 patients tested) and anti-Pneumococcal (111 of 239) immune responses. As expected many patients had evidence of sensitization to Aspergillus although specific IgG was not confined to those with evidence of allergic sensitization/allergic bronchopulmonary aspergillosis (ABPA). Eighteen of 277 patients tested had serological evidence of Strongyloides infection. Bacteria and/or yeast were cultured from the sputum in 76 out of 110 patients productive of sputum, and the most common microbes cultured were Candida sp. (44 patients), Staphylococcus aureus (21 patients), Haemophilus influenzae (18 patients). Conclusions: Many patients had evidence of infection, colonization, or sensitization to potential pathogens relevant to asthma. Strongyloides infection was evident in several patients, which may be a major issue when considering the risk of hyper-infection following immunosuppression and supports our local screening strategy.